1997
DOI: 10.1074/jbc.272.44.28102
|View full text |Cite
|
Sign up to set email alerts
|

The M r 18,000 Subunit of the Peripheral-type Benzodiazepine Receptor Exhibits Both Benzodiazepine and Isoquinoline Carboxamide Binding Sites in the Absence of the Voltage-dependent Anion Channel or of the Adenine Nucleotide Carrier

Abstract: The peripheral type benzodiazepine receptor (PBR) binds benzodiazepines such as RO5-4864 and isoquinoline carboxamide derivatives such as PK11195. This receptor includes an M r 18,000 isoquinoline-binding subunit predominantly located in mitochondrial membranes. This protein has been found to copurify with two other mitochondrial proteins, namely the outer membrane voltage-dependent anion channel (VDAC), also known as mitochondrial porin, and the inner membrane adenine nucleotide carrier. In vitro reconstituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 31 publications
3
30
0
Order By: Relevance
“…Hydropathy profile and experimental analysis have suggested that TSPO possesses a five-transmembrane structure (32,33), findings recently supported by electron cryomicroscopy of a bacterial homolog (34). Deletion of the C terminus of recombinant mammalian TSPO, which contains the CRAC motif, severely reduced cholesterol uptake when expressed in Escherichia coli, although PK 11195 binding was retained (25).…”
mentioning
confidence: 83%
“…Hydropathy profile and experimental analysis have suggested that TSPO possesses a five-transmembrane structure (32,33), findings recently supported by electron cryomicroscopy of a bacterial homolog (34). Deletion of the C terminus of recombinant mammalian TSPO, which contains the CRAC motif, severely reduced cholesterol uptake when expressed in Escherichia coli, although PK 11195 binding was retained (25).…”
mentioning
confidence: 83%
“…The binding of isoquinoline carboxamides and benzodiazepines is mutually competitive for the mBzR, and it was originally proposed that the binding site for benzodiazepines, such as the prototypical Ro 5-4864 (4′ Cl-diazepam), included the IBP, VDAC, and ANT (61). However, studies of yeast transformed with the IBP, but lacking either the VDAC or ANT protein, show high-affinity binding sites for isoquinoline carboxamides and benzodiazepines that are no different from binding sites of native receptors (62). More recently other proteins have been reported to associate with the IBP; these include the PBR-associated protein 1 [PRAX-1 (63)], the PBR-associated protein 7 [PAP7, or PKA with regulatory subunit 1α (64)], and a 10-kDa protein [pk10 (65)].…”
Section: Peripheral (Mitochondrial) Benzodiazepine Receptormentioning
confidence: 99%
“…The TSPO exists both as a monomer and as part of a multimeric complex involving several TSPO monomers with associated proteins, including the voltage-dependent anion channel (Boujrad et al, 1994(Boujrad et al, , 1996Rao and Butterworth, 1997). Although subunit interactions are not necessary for drug ligands to bind the TSPO monomer (Joseph-Liauzun et al, 1997;Lacapere et al, 2001), binding of some drugs to the TSPO is influenced by these interactions (Golani et al, 2001).…”
Section: Introductionmentioning
confidence: 99%